If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7z+5z-2=3z+9z+3-5
We move all terms to the left:
7z+5z-2-(3z+9z+3-5)=0
We add all the numbers together, and all the variables
7z+5z-(12z-2)-2=0
We add all the numbers together, and all the variables
12z-(12z-2)-2=0
We get rid of parentheses
12z-12z+2-2=0
We add all the numbers together, and all the variables
=0
z=0/1
z=0
| 4x+29x-2=7(4x+1) | | 17x-20=7x | | 6x+34x-10=8(5x+9) | | -15=-14t-15 | | 155n,n=8 | | O.5x=-1 | | 223=n-313 | | 7x+93=170 | | 6g+2g-6g+2g+4g=16 | | 259=152-w | | e+2=10 | | 35x+71=35x+18 | | -8.6z=3.78-8.4z | | g+42=91 | | 2m+30=18 | | t+12=3 | | 91/5-1/5=m-6.6 | | -7=8(-15+p)-2 | | 45x+3255-54x=66(50x+18) | | -8.6z=3.788 | | x-3/16=-1 | | 1.2x+5.4=7.2 | | 10c-8=42 | | 98=4x+3(2x+16) | | -1-c=19+c | | 22=8a=6-8 | | 16=-11-3w | | 6r30,r=5 | | -8p=-7p+17 | | 4(y-5)=2y+4 | | .50-20x=35 | | -20-9.4x=-10-9.9x |